An Analysis of The Meanings, Functions, and Strategies in The Translation of Idioms in The Movie Entitled The Avengers : Age of Ultron - ., Dewa Made Cipta Dwijaya; ., Drs. Asril Marjohan,MA; ., Dra.Ni Made Ratminingsih, MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengetahui makna, fungsi dan strategi yang digunakan dalam penerjemahan peribahasa dalam film yang berjudul The Avengers : Age of Ultron. Analisia peribahasa ini dilakukan karena kata – kata yang terikat dengan budaya bahasa atau dikenal dengan istilah peribahasa sangat menarik untuk dipelajari dan terkadang makna yang mereka tidak selalu sesuai dengan yang diungkapkannya. Peneliti menggunakan film sebagai sumber pengambilan data karena film memberikan gambaran tentang penutur bahasa asing dalam percakapanya sehari – hari dan film yang berjudul The Avengers : Age of ultron digunakan karena film ini merupakan film baru dan merupakan film yang paling tunggu – tunggu di tahun 2015. Tujuan dari penelitian ini adalah (1) untuk mengetahui makna dari peribahasa dalam film berjudul The Avengers : Age of Ultron, (2) untuk mengetahui fungsi peribahasa dalam film berjudul The Avengers : Age of Ultron dan (3) untuk mengetahui strategi penerjemahan peribahasa dalam film yang berjudul The Avengers : Age of Ultron. Desain penelitian ini adalah penelitian deskriptif kualitatif. Data tersebut dikumpulkan dengan menonton, mengidentifikasi dan mengklasifikaasi makna, fungsi dan strategi dalam penerjemahan peribahasa. Subjek dari penelitian ini adalah ScramCypher yang menyediakan transkripsi bahasa Inggris dan Indonesia untuk film tersebut. Hasil penelitian ini menunjukkan bahwa terdapat 83 peribahasa yang ditemukan dalam film tersebut. Makna dari peribahasa tersebut dianalisis menggunakan konsep kontekstual oleh Halliday (2010) dan dapat disimpulkan bahwa sebagian besar peribahasa tersebut menggunakan konteks situasi dalam penggunaannya dalam film tersebut. Fungsi peribahasa tersebut dianalisis menggunakan teori McCharty dan O’dell dan sebagian besar peribahasa tersebut memiliki fungsi untuk mengkomentari orang. Dalam analisa strategi penerjemahan, hanya 60 dari 83 peribahasa yang terjemahkan dengan benar dan strategi yang paling sering digunakan dalam penerjemahan tersebut adalah 1) translation by paraphrase, 2) using an idiom of similar meaning but dissimilar form, 3) using an idiom of similar meaning and form and 4) translation by omissionKata Kunci : Fungsi, Peribahasa, Makna, Strategi This study aims at finding out the meanings, functions and strategies used in the translation of idioms in movie entitled The Avengers : Age of Ultron. The analysis of the idioms was done because words which are culturally bound with language or known as idioms are very interesting to be learned and sometimes their meanings are not exactly as what they say. The researcher used a movie as a source of data collection because it gave a reflection of native speakers in their daily conversation and the movie entitled “The Avengers : Age of Ultron” is used because this is a brand new movie in 2015 and it is the highest grossing movie of 2015. The purposes of this research were: (1) to find the meanings of idioms in the movie entitled The Avengers : Age of Ultron, (2) to find out the functions of idioms in the movie entitled The Avengers : Age of Ultron, and (3) to find out the strategies used in the translation of idioms in the movie entitled The Avengers : Age of Ultron. This research was designed as a descriptive qualitative research. The data were collected through watching, identifying, and classifying the meanings, the functions and the strategies used in the translation of idioms. The subject in this study is ScramCypher who provided both English and Indonesian subtitles in the movie. The result of this study showed that there are 83 idioms found in the movie. The meanings of idioms were analyzed using contextual concepts of meaning by Halliday (2010) and it can be concluded that most of the idioms consider context of situation on its usage in the movie. The functions of idioms were analyzed using McCharty and O’dell theory and most idioms found in the movie functioned to comment on people. In analyzing the translation strategies, there were only 60 idioms out of 83 which were translated equivalently and the most frequent translation strategies used are 1) translation by paraphrase, 2) using an idiom of similar meaning but dissimilar form, 3) using an idiom of similar meaning and form and 4) translation by omissionkeyword : Function, Idioms, Meaning, Strategies.